ESRA19-0364 Stick before you stop – a visual prompt to perform stop before you block. (30th August 2019) - Small, J; Howell, M; Macfarlane, A; McKinlay, S
Abstract : Background and aims: An inadvertent wrong sided peripheral nerve block is a 'never event'. The Stop Before You Block (SBYB) campaign was developed in 2011 and is designed to eliminate these risk factors. SBYB should occur immediately before needle insertion. 1 In our department, wrong sided errors have occurred because staff, despite education, training and quality improvement projects, do not undertake SBYB 100% of the time. Methods: We incorporated a SBYB prompt and sticker into an adapted WHO surgical safety checklist sign-in. 2 The checklist, read out by the anaesthetic assistant, contains a prompt to attach the SBYB sticker to the block needle. This sticker then acts as an aide-memoire to carry out a SBYB immediately before needle insertion. We have carried out a staff questionnaire assessing knowledge and opinion. Results: 15 (40%) of all staff questioned admitted that the sticker had helped them remember to do a SBYB. Conclusions: It is important that continued effort is made to minimise the risk of wrong sided peripheral nerve blocks. A visual aid on the needle sheath should help to combat the factors contributing to these errors such as distraction in the anaesthetic room and a time delay after sign in. The most important factor, however, is the reminder in the WHO checklist. Without this, we believe staff would be just as likely to forget to use the sticker as previously, when commonly SBYB was forgotten. References: Stop Before You Block Campaign. https://www.rcoa.ac.uk/sites/default/files/CSQ-PS-sbyb-supporting.pdf WHO Surgical Safety Checklist and Implementation Manual. https://www.who.int/patientsafety/safesurgery/ss_checklist/en/